2015
DOI: 10.1160/th15-04-0330
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic diversity in the genetics of venous thromboembolism

Abstract: Genetic susceptibility is considered as a crucial factor for the development of venous thromboembolism (VTE). Epidemiologic and genetic studies have revealed clear disparities in the incidence of VTE and the distribution of genetic factors for VTE in populations stratified by ethnicity worldwide. While gain-of-function polymorphisms in the procoagulant genes are common inherited factors in European-origin populations, the most prevalent molecular basis for venous thrombosis in Asians is confirmed to be dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 105 publications
0
51
1
2
Order By: Relevance
“…26 Furthermore, a higher number of genetic variants predisposing individuals to VTE is found in Europe and America than in Asia. 22 patients also demonstrated that INR intensities of 1.8-2.4 appeared to be associated with the lowest incidence rate of major bleeding or TE events. 20 Other studies of venous TE (VTE) events have also demonstrated a lower prevalence rate in the Asian population than in the Caucasian population, 21,22 thus indicating a disparity in the thrombogenicity and response to warfarin between Asian and Western populations.…”
Section: Inr For Mvr Patients With High Cha2ds2-vascmentioning
confidence: 82%
“…26 Furthermore, a higher number of genetic variants predisposing individuals to VTE is found in Europe and America than in Asia. 22 patients also demonstrated that INR intensities of 1.8-2.4 appeared to be associated with the lowest incidence rate of major bleeding or TE events. 20 Other studies of venous TE (VTE) events have also demonstrated a lower prevalence rate in the Asian population than in the Caucasian population, 21,22 thus indicating a disparity in the thrombogenicity and response to warfarin between Asian and Western populations.…”
Section: Inr For Mvr Patients With High Cha2ds2-vascmentioning
confidence: 82%
“…Finally, whereas genetic factors for VTE have been studied somewhat extensively,19 the effect of environmental factors is much less understood. Studies conducted in Canada and the United States have found that immigration modifies the risk factor profile for many conditions in people from other countries, and that this is a time‐dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found a similar IR among immigrants from predominantly Black countries compared to White immigrants. This could potentially be explained, at least in part by differences in diet, body mass index and other variables between immigrants to Canada compared to United States residents, or by potential differences in recently described genetic markers for VTE in this group 19, 42. Until now, the burden of VTE was virtually unknown among groups of Latin America, Middle Eastern, African, or South Asian ancestry, with only a Swedish study evaluating a relatively small number of immigrants, mainly by country of origin 43.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and genetic risk factors of venous thrombosis vary significantly among different ethnic/racial groups [17][18][19]. For examples, the incidences per 100,000 of venous thrombosis were, respectively, 104 in the Caucasians and 21 in Asian-Pacific Islanders (P < 0.001) [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, these genetic variants do not confer susceptibility to venous thrombosis in the Chinese population. Instead, two variants of protein C gene (Arg-189 to Trp substitution, R189W, and Lys-192 deletion, K150del, leading to impaired anti-coagulant activity of protein C) and one variant of thrombomodulin gene (c.-151G > T, detected with the rs16984852 SNP, in the 5′ UTR, resulting in reduced thrombomodulin expression) increased risks toward venous thrombosis in the Chinese population [18,23,24]. Of all thrombotic events in our cohort, venous thrombosis was more prevalent (56.4%) than that of arterial thrombosis (43.6%), similar to the European cohort.…”
Section: Discussionmentioning
confidence: 99%